An object-oriented model for rapid prototyping of data path/control systems - a case study - Machado, Ricardo J. (1999)
Publicado em "Information control in manufacturing 1998 : (INCOM'98) : advances in industrial engineering : a proceedings volume from the 9th IFAC Symposium, Nancy-Metz, France, 24-26 June 1998. Vol. 2"